2019
DOI: 10.2217/epi-2019-0295
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA: Biogenesis, Degradation, Functions and Potential Roles in Mediating Resistance to Anticarcinogens

Abstract: Aim: This review aims to systematically describe the biogenesis and degradation of circular RNAs (circRNAs), discusses the major functions of circRNAs, introduces the mechanisms by which circRNAs play a role in cancer, comprehensively summarize the relationship between circRNAs and anticarcinogen resistance as well as underlying specific mechanisms in multiple cancers. Materials & methods: We screened and analyzed large quantity of scientific papers which associated with circRNAs, noncoding RNAs, function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 80 publications
(107 reference statements)
0
89
0
Order By: Relevance
“…CircATP8B4 was demonstrated to promote glioma radioresistance by serving as a miR-766 sponge, and circATP8B4 in EVs may be a potential biomarker for glioma radioresistance. It was reported that exosome-transmitted miRNA may promote chemosensitivity in multiple cancer types such as colorectal cancer and head and neck cancer (124,125), and recent studies have revealed that circRNAs mediate chemotherapy resistance in various types of cancer such as ovarian cancer and thyroid carcinoma (126)(127)(128). Hence, there is a novel hypothesis that exosomal circRNAs are influence chemotherapy resistance, but this still requires further experimental confirmation (Fig.…”
Section: Exosomal Circrnas Promote the Generation Of Premeta-mentioning
confidence: 99%
“…CircATP8B4 was demonstrated to promote glioma radioresistance by serving as a miR-766 sponge, and circATP8B4 in EVs may be a potential biomarker for glioma radioresistance. It was reported that exosome-transmitted miRNA may promote chemosensitivity in multiple cancer types such as colorectal cancer and head and neck cancer (124,125), and recent studies have revealed that circRNAs mediate chemotherapy resistance in various types of cancer such as ovarian cancer and thyroid carcinoma (126)(127)(128). Hence, there is a novel hypothesis that exosomal circRNAs are influence chemotherapy resistance, but this still requires further experimental confirmation (Fig.…”
Section: Exosomal Circrnas Promote the Generation Of Premeta-mentioning
confidence: 99%
“…circRNAs are endogenous non-coding RNA molecules that differ from linear RNA by their structure, a closed covalent loop lacking 3' or 5' polarity (13). circRNAs can sponge miRNAs through stable complementary binding and regulate gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are derived from mRNA precursors and characterized by the covalently closed-ring single strand without 5 ′ cap or 3 ′ poly A tail structure (6,7). CircRNAs functionally interact with RNA regulatory proteins (8), adjust the stability and expression of mRNAs (9), and have the potential of translation (10).…”
Section: Introductionmentioning
confidence: 99%